2020
DOI: 10.1242/dev.177964
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical feedback-loop regulation of morphogenesis in plants

Abstract: Morphogenesis is a highly controlled biological process that is crucial for organisms to develop cells and organs of a particular shape. Plants have the remarkable ability to adapt to changing environmental conditions, despite being sessile organisms with their cells affixed to each other by their cell wall. It is therefore evident that morphogenesis in plants requires the existence of robust sensing machineries at different scales. In this Review, I provide an overview on how mechanical forces are generated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 112 publications
(160 reference statements)
1
37
0
Order By: Relevance
“…Thus, cellular cAMP levels may have profound effects for the proper functionality of plants, which is evident by the results discussed above. Many biologic processes in plants employ feedback-loop regulation to maintain homeostasis or dynamic equilibrium, including hormone metabolism, morphogenesis, and photosynthesis [ 195 , 216 , 217 , 218 ], which obviously warrant an optimal outcome of functions. In animals, it was shown that initially higher levels of cAMP promote cell survival and slow down retinal degeneration, but elevated cAMP levels may ultimately become toxic [ 200 ]; additionally, cAMP elevation was found to improve the signal-to-noise ratio in amphibian rod photoreceptors during the sensory transduction of the visual system [ 219 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cellular cAMP levels may have profound effects for the proper functionality of plants, which is evident by the results discussed above. Many biologic processes in plants employ feedback-loop regulation to maintain homeostasis or dynamic equilibrium, including hormone metabolism, morphogenesis, and photosynthesis [ 195 , 216 , 217 , 218 ], which obviously warrant an optimal outcome of functions. In animals, it was shown that initially higher levels of cAMP promote cell survival and slow down retinal degeneration, but elevated cAMP levels may ultimately become toxic [ 200 ]; additionally, cAMP elevation was found to improve the signal-to-noise ratio in amphibian rod photoreceptors during the sensory transduction of the visual system [ 219 ].…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that these expand both in diameter and spacing upon deesterification, leading to cell growth and shape formation. Oddly, these nanofilaments were not observed in the periclinal walls of the same cells despite the physical continuity between anticlinal and periclinal walls and although the latter are generally considered to be crucial in pavement-cell morphogenesis [54][55][56] . Alternative explanations for the patchy pattern of pectin label in the anticlinal walls, such as nano-wrinkles or locally heterogeneous distribution because of the presence of well-documented vertical cellulose microfibrils 57,58 , were not further explored and, therefore, true cause-effect relationships remain to be explored.…”
Section: Cytoskeletal Coordination Of Cell Wall Assemblymentioning
confidence: 93%
“…Alternative explanations for the patchy pattern of pectin label in the anticlinal walls, such as nano-wrinkles or locally heterogeneous distribution because of the presence of well-documented vertical cellulose microfibrils 57,58 , were not further explored and, therefore, true cause-effect relationships remain to be explored. The lack of consensus around the fundamental underpinnings of plant cell growth points to the need to address basic questions with regards to cell wall biochemistry and cell differentiation 55,56 .…”
Section: Cytoskeletal Coordination Of Cell Wall Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…RG II, on the other hand, has a α 1,4-linked Gal backbone, has structurally complex side chains composed of a number of different sugars. It influences the mechanical properties of cell walls through ionic interactions with boron which help to crosslink RG II [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%